Luces y sombras de la vida monástica femenina: las concepcionistas de Cuenca (Ecuador) en el siglo XVIII - Viforcos Marinas, María Isabel (Estudios humanísticos. Geografía, historia y arte, 1995)
This study is intended to contribute to our knowledge of life in women’s religious orders in Latin America at the time of the Spanish Viceroys. In this way it offers an approach to the religious life and the mentality of colonial society.